Three cases of isolated terminal deletion of chromosome 8p without heart defects presenting with a mild phenotype1. Issue 4 (12th March 2013) - Burnside, Rachel D.; Pappas, John G.; Sacharow, Stephanie; Applegate, Carolyn; Hamosh, Ada; Gadi, Inder K.; Jaswaney, Vikram; Keitges, Elisabeth; Phillips, Karen K.; Potluri, Venketaswara R.; Risheg, Hiba; Smith, Janice L.; et al.
Abstract Individuals with isolated terminal deletions of 8p have been well described in the literature, however, molecular characterization, particularly by microarray, of the deletion in most instances is lacking. The phenotype of such individuals falls primarily into two categories: those with cardiac defects, and those without. The architecture of 8p has been demonstrated to contain two inversely oriented segmental duplications at 8p23.1, flanking the gene, GATA4. Haploinsufficiency of this gene has been implicated in cardiac defects seen in numerous individuals with terminal 8p deletion. Current microarray technologies allow for the precise elucidation of the size and gene content of the deleted region. We present three individuals with isolated terminal deletion of 8p distal to the segmental duplication telomeric to GATA4. These individuals present with a relatively mild and nonspecific phenotype including mildly dysmorphic features, developmental delay, speech delay, and early behavior issues. © 2013 Wiley Periodicals, Inc.